Nieznośna lekkość pocieszenia, nieznośna miałkość protestu. Internetowe zmartwychwstania Aylana Kurdiego - Jakubowski, Piotr (Załącznik Kulturoznawczy, 2023)
The aim of this article is to critically analyze the internet’s remixes of Nilüfer Demir’s photography showing the dead body of Aylan Kurdi – a 3-year oldSyrian refugee – found on the beach near Turkish city Bordum. The main question here is: how the convergence culture ‘regards the pain of the other’ and deals with it? Semiotic analysis of chosen examples leads to a conclusion that while some artists undertake a specific visual tactics of protest and objection, more often, and even in clearly critical pictures, the ‘rhetoric of consolation’ is a predominating one and serves to both artists’ and viewers’ complacency and consoling. Terror of the pain and death is deleted from those images and replaced by cheap and idle tenderness or even kitsch.